Room of Hazards: An Interprofessional Evaluation of Safety Risks in a Simulated Patient Room. Issue 1 (January 2022) - Wang, Melinda; Bilan, Victor P.; McCullough, Megan; Banda, Barbara; Merchant, Naseema B.; Rodwin, Benjamin A.
Abstract : Objectives: Approximately 3.7% of patients experience adverse events in health care facilities, many of which are preventable. Patient safety requires effective training and an interprofessional culture of safety, but few studies compare the safety skills of different hospital professions. We sought to assess skills in safety hazards identification among staff from different health care disciplines with a pilot study. Methods: An exercise with a simulated room of an inpatient ward with a patient mannequin in a hospital bed with 34-intentionally planted safety hazards was set up. Health care staff members from various professions walked around the room and independently documented observed safety hazards. Identified hazards were separated based on staff disciplines, grouped into 5 categories (patient, medications, equipment, environment, care processes), and analyzed using analysis of variance. Because participants identified more hazards than the 34 intentionally planted hazards, these were analyzed separately. Results: The study included 111 staff: nurses (n = 68), nursing students (n = 5), medical students (n = 3), physicians (n = 11), social workers (n = 5), pharmacists (n = 6), certified nursing assistants (n = 9), and psychologists (n = 4). There were significant differences among professions in the following categories: medications, equipment, and total number of safety hazards ( P < 0.05 for all). Nurses found more intended equipment hazards than did social workers (38.8% versus 4.4%, P < 0.001), pharmacists (38.8% versus 11.1%, P = 0.004), medical students (38.8% versus 7.4%, P = 0.021), and psychologists (38.8% versus 8.3%, P = 0.001) and more medication hazards than nursing students (20.3% versus 16.7%, P = 0.008), whereas certified nursing assistants also found more equipment hazards than did social workers (25.9% versus 4.4%, P = 0.016). Conclusions: There were significant differences in patterns of safety hazards identified among health care professions, with nurses identifying more hazards than several other professions. This finding suggests that each health care profession's unique training and responsibilities result in varying ability to identify safety hazards and that interdisciplinary safety teams may be more effective than those from only a single profession. Our study provides a starting point to encourage diversification of hospital professions in simulation-based safety trainings, although further work is needed to validate these findings moving forward.